DAMPAK KEBIJAKAN DALAM JARINGAN TERHADAP PELAKSANAAN PEMBELAJARAN PENDIDIKAN DASAR PADA MASA PANDEMI COVID-19 DI KABUPATEN KONAWE UTARA - Jopang; La Bilu; Amin Tunda (Journal Publicuho, 2023)
The purpose of this study was to find out and analyze the impact of online policies on the implementation of basic education learning during the Covid-19 pandemic in the North Konawe Regency Region. This study uses a qualitative approach. The data processing procedure used follows the interactive data analysis model of Miles & Huberman (1994) which includes four interrelated sub-processes, namely data collection, data reduction, data display, and conclusion drawing/verification.The results of the study show the impact of online policies on the implementation of basic education learning during the Covid-19 pandemic in North Konawe Regency, including (1) Impacts on teachers, including; (a) teachers have difficulty managing PJJ and tend to stage the curriculum; (b) study time is reduced so that teachers do not meet teaching hours; (c) teachers have difficulty communicating with parents and other partners at home. (2) The impact on students includes: (a) Students quickly get bored and bored; (b) students' mood in learning goes up and down; (c) the assessment given by the teacher is not fair; (d) students cannot operate Android (HP); (e) the child's learning achievement decreases; (f) parents do most of the tasks; (g) the child's psychosocial condition decreases and (h) there is covert violence against students. (3) The impact on students' parents is as follows: (a) the role of parents increases; (b) economic difficulties in buying pulses and cellphones; (c) time to supervise and accompany children at home.